Coastal Impact From High-Energy Events and the Importance of Concurrent Forcing Parameters: The Cases of Storm Ophelia (2017) and Storm Hector (2018) in NW Ireland - Guisado-Pintado, Emilia; Jackson, Derek W. T. (Frontiers in Earth Science, 2019)
Infrequent but high energy storm events can radically modify coastlines, at times displacing significant sediment volumes and changing shoreline configuration. More frequent and stronger Atlantic storms over the last 40 years have heightened the potential risk to coastal environments, population and infrastructure. Understanding local environmental forcing conditions and associated variables involved in coastal impact and response, can better inform future coastal management planning. This study examines the coastal impacts of two separate storms that occurred at Five Finger Strand, on the northwest Irish coast, in late 2017 (Storm Ophelia) and mid-2018 (Storm Hector). Using forcing parameters (wind speed and direction, wave heights and wave run up) along with 3D topographic surveys, impacts are examined for both storm events. For Storm Ophelia, shore-oblique to shore-parallel waves (2 m in height) coincident with low tide (∼0.8 m) were recorded. This resulted in minimal erosional impact which was corroborated by a new proxy storm impact index, “Storm Dune Trimming” (value of >0.03) as well as a sediment displacement volume of 8,300 m3, largely confined to the intertidal area with only limited foredune edge erosion. Storm Hector, on the other hand, a lower energy event than Storm Ophelia, resulted in much more pronounced sediment displacement (13,400 m3 in the intertidal area) and significantly more dune scarping (Storm Dune Trimming >0.09) due to better synchronicity of forcing factors such as high tide level, high wave heights and onshore wind direction. We conclude that storm energy is not always a direct indicator of coastal impact and that synchronicity of local forcing factors and antecedent beach conditions appears to be the most relevant in actual coastal response on sandy beaches. This study, therefore shows the importance of particular environmental parameters and their simultaneous timing in forcing change and is an important insight into which parameters may be more risk-relevant in producing erosion along many sandy, dune-fringed coasts of NW Europe.